OP85 Fruit and Vegetable Consumption and Mortality: A Cox Regression Analysis. (10th September 2013) - Oyebode, O; Gordon-Dseagu, V; Walker, A; Mindell, J
Abstract : Background: Following World Health Organisation recommendations, the UK government promotes a daily intake of at least five portions of fruit and vegetables. Methods: We used Cox regression to estimate hazard ratios and 95% confidence intervals for an association between fruit and vegetable consumption and all-cause, cancer and cardiovascular (CVD) mortality, adjusting for age, sex, BMI and social class in data from 85, 347 adult participants in the Health Survey for England 2001-2008. Results: Fruit and vegetable consumption had a substantial protective effect for all-cause mortality (adjusted HR for 6-<7 portions 0·64 (95% CI 0·54–0·76)), stronger when deaths within a year of baseline were excluded (HR 0·57 (0·45–0·72) or when fully-adjusting for physical activity (0·48 (0·36–0·66). Consumption was significantly associated with reduced cancer (HR for 5- < 7 portions 0·78 (0·63–0·96) and CVD mortality, with increasing benefits being seen up to more than seven daily portions of fruit and vegetables for CVD (0·69 (0·53–0·89)). Consuming up to three to four portions of fruit daily and up to 3 + portions of vegetables a day was associated with decreased mortality. Vegetables had a greater effect than fruit (HR for 2- < 3 portions 0·82 (0·74–0·91) and 0·91 (0·83–0·99) respectively). Conclusion: There is no threshold for the association between fruit and vegetable consumption and CVD survival up to a total of seven portions daily. Maximal benefit was conferred by six daily portions for all deaths and five portions for cancer. Vegetables have greater benefit than fruit.